Music as a transpersonal care tool - perceptions of hospitalized people assisted in the university extension - Emanuelle Caires Dias Araújo Nunes; Fabiana Aguiar de Oliveira; Juliana Xavier Pinheiro da Cunha; Sabrina Oliveira Reis; Gizelia da Gama Meira; Regina Szylit (Universidade Federal do Rio de Janeiro, 2020)
ABSTRACT Objective: to analyze the perception of hospitalized patients about the care received through an extensionist musical visit under the perspective of the Theory of Human Caring. Method: a descriptive-exploratory-qualitative research conducted in a hospital of the state of Bahia, with 15 hospitalized patients, interviewed within 24 hours after receiving the extensionist musical visit. Collection involved semi-structured interview, analyzed through Discourse of the Collective Subject. Results: three axes emerged: Musical Care at the interface with Transpersonal Care; Music as a rescue element of hope during hospitalization; and Beyond music - a meeting between care, art and human relations. The results show the feelings evoked during the experience of the musical visit and emphasize the importance of this activity. Conclusion and Implications for the practice: music as a Transpersonal Care strategy motivates patient-staff-family ties, encouraging optimism and hope by mobilizing feelings and sensations of body, mind and soul, enabling the emergence of resilient behaviors during the hospitalization process. The study promotes reflection and guidance for the most creative, sensitive and bold care in the hospital environment. It suggests greater use of music by the health staff - meeting a care extended to human needs that transcend the physical.